Optimization of Machining Process Parameters Using Moora Method - Iqbal, Mohd; Hameedullah, M.; Abhang, Laxman B. (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2020)
A multi-response optimization is a popular tool in many economic, managerial, constructional, manufacturing, process design, product design technologies, machinery and system, devices, process parameters etc. This research paper demonstrates the application of a simple multi-objective optimization on the basis of ratio analysis (MOORA) method to solve the multi-criteria (objective) optimization problem in the machining process. In this paper, the chip-tool interface temperature, main cutting force, and tool wear rate were investigated in various machining conditions in turning operations. Various machining parameters, such as the cutting speed, feed rate, and depth of cut and effective tool inserts nose radius, were considered. Composite factorial design (24+8) was used for experimentation. Multiple response values were obtained using actual experimentation. By using these experiments, two different methods were proposed. Machining parameters were optimized by minimizing chip-tool interface temperatures, tool wear rate, and main cutting force during machining of alloy steel. The results obtained using the MOORA method almost agree with the grey relational analysis method which shows the authenticate applicability, potentiality, and flexibility of MOORA method for solving various complex decision-making problems in present-day manufacturing industries.